ANALISIS FAKTOR EKSTERNAL DAN FAKTOR INTERNAL PERUSAHAAN YANG MEMPENGARUHI AUDIT DELAY (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di Indeks Saham Syariah Indonesia Pada Tahun 2013-2019) - Warno Warno (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
Abstract: The study aims to examine empirically the effect of the application of IFRS, size KAP,company size, profitability, solvability, complexity company to audit delay on manufacturing companies in Indeks Saham Syariah Indonesia (ISSI). The population in this study is manufacturing companies registered in Indeks Saham Syariah Indonesia (ISSI) in 2013-2019. The research sample was taken using a purposive sampling method in which of the  163 companies selected according to the criteria as mush as 51 companies. The analysis method of this study uses multiple linier regression. The result of this study indicate that application of IFRS application of IFRS had positive and significant effect. While complexity company had negative significant to audit delay. Size KAP and profitabilitas had negative not significant effect, company size and solvability had positive not significant effect to audit delay.